Growth rate and mortality of selais fish (Ompok hypophthalmus) in the waters of the Indragiri River Lubuk Terentang Village, Gunung Toar District, Kuantan Singingi Regency, Riau Province - Intan Nikita Syailta Yenti; Eni Sumiarsih; Nur El Fajri (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2021)
Abstrack        Ompok hypophthalmus is one of the caught fish commonly found in the Indragiri River, Lubuk Terentang Village. The purpose of this study was to determine the rate of growth and mortality of Ompok hypophthalmus. Fish sampling was carried out for 10 days in February and 10 days in March by using drift nets and nets. Data were analyzed by ELEFAN I method, FiSAT II software (FAO-ICLARM Fish Stock Assessment Tool). There were 109 fish caught. The results showed that the growth pattern of fish was negative allometric. Long frequency distribution ranges from 150 to 261 mm. The results of the Von Bertalanffy growth equation show that Lt = 260.40 (1-e-1,2(t+0.073)). This means the asymptote length (L∞) of the hypophthalmic is 260.40, the growth coefficient (K) 1.2 per year and the theoretical age (t0) of fish is equal to 0.073. The total mortality (Z) of fish is 1.88 per year. The estimated natural mortality (M) of fish is 1.09 per year and deaths due to capture (F) of 0.79 per year. The exploitation rate (E) of fish is 0.42 and shows this value is still below the optimum exploitation rate of 0.50.Keywords: Selais Fish, Ompok hypophthalmus, Growth Rate, Mortality, Indragiri River, Lubuk Terentang Village